BREAKWATER DESIGN WITH SOIL IMPROVEMENT OF BAMBOO PILE MATRASS AND PREFABRICATED VERTICAL DRAIN AND SLOPE STABILITY ANALYSIS BECAUSE OF EMBANKMENT IN RECLAMATION AREA NEW TANJUNG PRIOK PORT - OKTAVIANUS SIMBOLON, MIKHAEL
The function of Breakwater in this project is to protect reclamation area that will be a terminal container and product in New Tanjung Priok Port. The type of breakwater is rubble mound consisting of three layer, armor with A-Jack material 2.5 ton, underlayer with gravel material 250 kg, and core with gravel material 50-75 kg. Design of breakwater dimension is according to the wave of height and period significant with 500 years return period and 50 years design life.The soil improvement of Breakwater is bamboo pile matrass and prefabricated vertical drain (PVD) which install on bamboo cluster. While the soil improvement of reclamation is PVD and preloading method. Breakwater and preloading construction process will be staging to increase the bearing capacity of soil (gained strength) because of consolidation process. The calculation of degree of consolidation use Hansbo method for radial drainage and Carrillo method for combination of vertical and radial drainage. The calculation of settlement use equivalent raft method by assumption that bamboo pile matrass is a pile raft. Slope stability analysis because of the sand embankment and preloading will use Plaxis AE with effective parameters and Geoslope 2007 with total parameters of soil. In Plaxis, bamboo cluster modelling as embedded pile row, bamboo matrass as plate element, and plane-strain permeability of soil effect of PVD installation will use the method proposed by Indraratna. Earthquake design for seismic slope analysis, use screening analysis method and the method proposed by Hynes-Griffin and Franklin. The results of slope stability analysis by Plaxis and Geoslope show that for temporary condition, pseudostatic condition, and long term condition, all of safety factor are sufficient.